The Effect of Long-Term Use of Custom Insole on Agility in Adult Flat Foot Case - Setyawan, Dwi; Fatati, Muhibbah (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: Adult Flat foot is a condition in which the foot does not have the normal arch of the foot and occurs in adulthood. Someone who experiences flat feet will tend to decrease the quality of walking, including activities that require agility or agility. One of the treatments that can be given for flat foot cases is the provision of a custom insole in the form of medial arch support. Medial arch supports are designed to control the alignment and function of the foot and lower limbs and are used to limit movements such as overpronation. Objective: To decide the long-term impact of utilizing custom insoles on nimbleness in grown-up flat-foot cases. Method: The inquiry about the plan could be a quasi-experimental sort of investigation with a one-group pre and post-test. The research subjects were 18 students who experienced flat feet. Each investigated subject was given a custom insole mediation for six months and observed every two months. Information examination in this consideration utilised the Combined Tests T-test and the Wilcoxon test. Results: Statistically, there was a significant effect on the use of custom insole on agility as measured by the EST method (t = -3.05, p-value = 0.002), measured by the T-Test method (t = 5.91, p-value = 0.000), and measured by the IAT (z = -2.21, p-value = 0.016). Conclusions: The use of a custom insole affects increasing agility in flat foot conditions, so it is recommended to use a medial arch support in flat foot conditions.